Anak Laki-laki Tidak Boleh Menangis?: Bias Gender Pengasuhan Anak Usia Dini - Siron, Yubaedi; Asbi, Sherllyn Azzaharra; Amalia, Putri Rizki; Cahyani , Laila (Early Childhood Islamic Education, 2023)
In Indonesia, gender perception misconceptions remain prevalent. The parenting styles of children are affected by the gender perceptions of their parents. This study aims to describe the gender biases experienced by parents in childcare settings. This study uses a mixed method by distributing questionnaires and conducting structured interviews. This study involved 204 parents with kids aged 0 to 8. Quantitative data analysis uses descriptive statistics, while qualitative data analysis applies to Miles and Huberman. According to the findings of this study, 27.1% of parents had a gender-responsive parenting style. However, 72.9% of parents appear to consider themselves gender bias. This condition happened because culture and environment continue to influence parents' perceptions.